Innovation technologique et pratiques domestiques : analyse d'une expérience domotique - Beillan, Véronique (Sociétés contemporaines, 1994)
À partir du suivi sociologique d'une expérience domotique portant sur quinze logements du secteur HLM, cette étude traite des conditions d'appropriation sociale d'une nouvelle technologie domestique. Après un exposé de la méthode de recueil des données, basée sur la réalisation de trois vagues ď entretiens - réparties sur trois ans - auprès des ménages du lotissement domotique, l'article présente les premiers résultats ainsi que les nouvelles pistes de recherche à approfondir lors de la troisième et dernière phase du suivi. L'analyse comparative des deux premières vagues d'entretiens a permis de noter la permanence des attentes et des attitudes des ménages à l'égard de la domotique mais aussi le caractère hétérogène et ambivalent de ces dernières. Des freins ď ordre socio-économique et socio-culturel à l'intégration sociale de la technique ont été identifiés. Ainsi, des liens se dessinent entre l'automatisation des tâches et certains éléments tels que le statut et l'identité de la femme, l'organisation et la hiérarchisation des activités domestiques, les pratiques de délégation et ď externalisation du travail domestique.
Keywords: 1900-1999; 1980-1989; 1990-1999; approches et analyses; care; cours; discipline; europe; france; inégalités; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique

Feminism and postmodernism - Ferguson, Margaret; Wicke, Jennifer (Duke University Press, 1994)
This collection of essays explores the significant agreements and tensions between contemporary feminist and postmodern theories and practices. Having brought enormous changes to conceptions of the body, identity, and the media, postmodernity compels the rethinking of many feminist categories, including female experience, the self, and the notion that "the personal is political." Feminist analysis has been equally important, though not always equally acknowledged, as a force within postmodernism. Feminist writings on subjectivity, master narratives, and the socioeconomic underpinnings of the master narrative of theory itself have been particularly influential. This volume traces the crossings and mutual interrogations of these two traditions into the arenas of cultural production, legal discourse, and philosophical thought. Multidisciplinary and international in their collective focus, the essays range from a study of Madonna as an Italian American woman who is revising the cultural meanings of an ethnic feminism to a unique interview with Mairead Keane, the national head of the Women’s Department of the Irish political party Sinn Fein. Turning the prism of postmodern feminism onto such diverse cultural objects as literary and literary critical texts, contemporary film, and music, these essays intervene in debates regarding technology, sexuality, and politics. Challenging modern feminisms to articulate their inescapable relation to postmodern society, this expanded edition of a special issue of boundary 2 also explores ways in which feminism can work as the cutting edge of a global postmodernism. Contributors. Salwa Bakr, Claire Detels, Margaret Ferguson, Carla Freccero, Marjorie Garber, Barbara Harlow, Laura E. Lyons, Anne McClintock, Toril Moi, Linda Nicholson, Mary Poovey, Andrew Ross, David Simpson, Kathyrn Bond Stockton, Jennifer Wicke
Keywords: amériques; approches et analyses; cours; discipline; fem1000; féminisme pop; irlande; philosophie; postmodernisme; premier cycle; régions géographiques; sciences humaines; troisième vague; états-unis; études culturelles